Effect of Training Healthcare Providers in Helping Babies Breathe Program on Neonatal Mortality Rates - Mayer, Maria M.; Xhinti, Nomvuyo; Mashao, Lolly; Mlisana, Zolile; Bobotyana, Luzuko; Lowman, Casey; Patterson, Janna; Perlman, Jeffrey M.; Velaphi, Sithembiso (Frontiers in Pediatrics, 2022)
Background: Training on Helping Babies Breathe (HBB) Program has been associated with reduction in early neonatal mortality rate (ENMR), neonatal mortality rate (NMR) and fresh stillbirth rate (FSBR) in low- and middle-income countries (LMICs). This program was implemented in five different healthcare facilities in the Oliver Reginald Tambo (ORT) District, South Africa from September 2015 to December 2020. Objective: To determine and compare the FSBR, ENMR and NMR between 2015 before initiation of the program (baseline) and subsequent years up to 2020 following the implementation of facility-based training of HBB in five hospitals in ORT District. Methods: Records of perinatal statistics from January 2015 to December 2020 were reviewed to calculate FSBR, ENMR and NMR. Data were collected from the five healthcare facilities which included two district hospitals (Hospital A&B), two regional hospitals (Hospital C&D) and one tertiary hospital (Hospital E). Comparisons were made between pre- (2015) and post- (2016-2020) HBB implementation periods. Differences in changes over time were also assessed using linear regression analysis. Results: There were 19275 births in 2015, increasing to 22192 in 2020 with the majority (55.3%) of births occurring in regional hospitals. There were significant reductions in ENMR (OR-0.78, 95%CI 0.70-0.87) and NMR (OR- 0.81, 95%CI 0.73-0.90), but not in FSBR, in the five hospitals combined when comparing the two time periods. Significant reduction was also noted in trends over time in ENMR (r2=0.45, p=0.001) and NMR (r2=0.23, p=0.026), but not in FSBR (r2=0.0, p=0.984) with all hospitals combined. In looking at individual hospitals, Hospital A (r2=0.61, p<0.001) and Hospital E (r2=0.19, p=0.048) showed significant reduction in ENMR over time, but there were no significant changes in all mortality rates for Hospital B, C and D, for district or regional hospitals combined. Conclusion: There was an overall reduction of 22% and 19% in ENMR and NMR respectively from pre- to post-HBB implementation periods, although there were variations from year to year over the five-year period and, across hospitals. These differences suggest that there were other factors that affected the perinatal/ neonatal outcomes in the hospital sites in addition to implementation of training in HBB.